Efektivitas Pupuk Bio organik Terhadap Produksi Tanaman Semangka (Citrullus vilgaris L.) di Desa Sungai Tunu Barat Kecamatan Ranah Pesisir Kabupaten Pesisir Selatan - Hayani, Hayani; Rizki, Rizki; Novi, Novi (Pendidikan Biologi, 2013)
ABSTRACTWatermelon (Citrullus vulgaris L.) is one fruit crop is popular because it tastes sweet, crisp and a lot of water content. Requirement of watermelon continues to increase while the production is still low.Â  Economic value of watermelon is quite high and is expected to increase revenues society therefore to increase the production of watermelon cultivation needs to be done. Watermelon cultivation using organic bio fertilizers other environmentally friendly can also add soil organic matter and very simple acquiring. The objectives of this research is to determine the effectiveness of Bio organic fertilizer for crop production of watermelon (Citrullus vulgaris L.)Â  which includes: fruit weight, fruit diameter and number of pieces. This research has been conducted on farmers field Tunu River Village Sub Domains West Coast South Coastal District from April to June 2013. This type of research is experimental, this study using Cluster Randomized Design (RAK) with 4 treatments and 6 repetitions, each treatment is a control (Urea, NPK, SP36 and KCL), B (Bio Organic 2%), C (4% organic Bio), D (6% organic Bio) parameters measured were fruit weight, fruit diameter and number of pieces. Data were processed using analysis of variance and continued DNMRT test at level 5%. The results were analyzed by analysis of variance after directing that the use of Bio organic fertilizer is not a real effect on crop production covering a total of watermelon fruit, fruit weight and fruit diameter compared dangan use of inorganic fertilizers. From the research results it is advisable for farmers to use organic bio fertilizer in crop cultivated watermelon pupuknya for more economical and environmentally friendly.